Determination of the 95% effective dose of remimazolam tosylate in anesthesia induction inhibits endotracheal intubation response in senile patients - Qu, Liangchao; Liu, Mei; Ouyang, Ru; Li, Tianyuan; Long, Dingde; Jiang, Yao; Wang, Chengyu; Cheng, Liqin (Frontiers in Pharmacology, 2023)
BACKGROUND AND PURPOSE The prevalence of elderly patients prompts anesthesiologists to determine the optimal dose of medication due to the altered pharmacokinetics and pharmacodynamics of this population. The present study aimed to determine the 95% effective dose (ED95) of remimazolam tosylate in anesthesia induction to inhibit endotracheal intubation-related cardiovascular reaction in frail and non-frail senile patients. METHODS A prospective sequential allocation dose-finding study of remimazolam tosylate was conducted on 80 elderly patients who received general anesthesia between May and June 2022 at the First Affiliated Hospital of Nanchang University. The initial dose was 0.3 mg/kg. The blood pressure and heart rate fluctuations during intubation were either <20% (negative cardiovascular response) or ≥20% (positive cardiovascular response). If positive, the dose of the next patient was increased by 0.02 mg/kg, while if negative, it was reduced by 0.02 mg/kg according to the 95:5 biased coin design (BCD). The ED95 and 95% confidence intervals (CIs) were determined using R-Foundation isotonic regression and bootstrapping methods. RESULTS The ED95 of remimazolam tosylate to inhibit the response during tracheal intubation was 0.297 mg/kg (95% CI: 0.231–0.451 mg/kg) and 0.331 mg/kg (95% CI: 0.272–0.472 mg/kg) in frail and non-frail senile patients, respectively. CONCLUSIONS AND IMPLICATIONS The CI of the two groups overlap, and no difference was detected in the ED95 of remimazolam tosylate in inhibiting endotracheal intubation-related cardiovascular response in frail and non-frail senile patients. These results suggested that remimazolam tosylate is an optimal anesthesia inducer for all elderly patients.